Luminescence of AlN:Mn2+ materials: Properties and mechanisms - Ruska, Rihards; Berzina, Baiba; Cipa, Janis; Trinkler, Laima; Sarakovskis, Anatolijs; Grabis, J.; Steins, I. (Elsevier, 2023)
Luminescence processes resulting in 600 nm emission of Mn2+ ions in AlN:Mn ceramics were studied based on investigations of photoluminescence and its excitation spectra, luminescence kinetics and long-lasting luminescence (PersL) properties. For AlN:Mn2+ nanopowders, the photoluminescence spectra and PersL were studied. Luminescence properties were examined and compared after the samples were irradiated with 520 nm light, resulting in direct excitation of Mn2+ ions, thus causing the intra-center luminescence, or with 263 nm light. As known, in the last case, the oxygen-related defects are primarily excited with the following energy transfer to Mn2+ ions and 600 nm emission, thus forming the recombination luminescence (RecL). Two types of excitations of the 600 nm RecL were used. In the first case, the luminescence response was detected during the sample irradiation with 263 nm light. It was found that at RT, the decay of the RecL is fast and its decay constant τ = 1.2 ms coincides with the value obtained for the intra-center luminescence. A time-dependent rise of the 600 nm luminescence intensity under 263 nm excitation was observed. In the other case, the 600 nm RecL was detected when irradiation of the sample with 263 nm light was ceased, and spectra and decay of PersL were studied. It was found that the decay of 600 nm PersL spectra could be described using three exponential functions, thus manifesting a variety of luminescence processes. The results allow tracing of the luminescence processes and proposal of the mechanisms resulting in the 600 nm light emission of Mn2+ ions. An energy level scheme of AlN:Mn2+ was constructed to elucidate of the luminescence processes and mechanisms. --//-- R. Ruska, B. Berzina, J. Cipa, L. Trinkler, A. Sarakovskis, J. Grabis, I. Steins, Luminescence of AlN:Mn2+ materials: Properties and mechanisms, Results in Optics, Volume 10, 2023, 100365, ISSN 2666-9501, https://doi.org/10.1016/j.rio.2023.100365. (https://www.sciencedirect.com/science/article/pii/S2666950123000172) Published under the CC BY-NC-ND lilcence.
This research is funded by the Latvian Council of Science grant No. LZP (FLPP)-2019/1–0443. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-Teaming Phase 2 under grant agreement No. 739508, project CAMART2.
Keywords: Manganese doped aluminum nitride; Ceramics; Nanopowder; Photoluminescence and excitation spectra; Luminescence kinetics; Luminescence mechanisms; Persistent luminescence